METTL3-mediated HPV vaccine enhances the effect of anti PD-1 immunotherapy to alleviate the development of cutaneous squamous cell carcinoma - Yingjie Zhang; Yiru Wang; Shuping Guo; Hongzhou Cui (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Cutaneous squamous cell carcinoma (cSCC) develops from epithelial keratinocytes by dysregulation of self-renewal and differentiation. Recent studies have found that the size and number of cSCC tumors gradually decrease or even disappear after HPV vaccination. However, the role of the HPV vaccine in the cSCC mechanism is poorly understood. Objective The aim of this study is to investigate the effect and mechanism of the HPV vaccine in cSCC. Methods Immunofluorescence was used to study the immune infiltrating cells in the tumor tissues of patients with cSCC. The effects of the HPV vaccine on cSCC cells and tissues were studied by Cell Culture, Real-time PCR, Western Blot, Cytotoxicity Assay, Enzyme-linked Immunosorbent Assay, m6A Blotting, CCK-8 Assay, m6A Ribonucleic acid Methylation Quantification and tumor transplantation. Results The HPV vaccine enhanced the toxic effect of CD8+T cells on cSCC cells and promoted the secretion of multiple cytokines by CD8+T cells. In addition, HPV vaccines can increase tumor sensitivity to anti-PD-1 therapy by downregulating METTL3 in tumor tissue, with the combination of HPV vaccine and PD-1 monoclonal antibodies producing enhanced immune cell infiltration compared to PD-1 blockade alone. Study limitations It is important to note the limitations of this study, including the small sample size, the construction of the mouse model, and the choice of HPV vaccine and PD-1 monoclonal antibody, which may limit the generalization of our findings to a wider population. Conclusions It is hoped that this research will contribute to a deeper understanding of the role of the HPV vaccine in the treatment of cSCC. HPV vaccine is expected to become an important approach to alleviate the development of cSCC.